AB0641 VITAMIN D SERUM LEVELS AND THE RISK OF DIGITAL ULCERS IN SYSTEMIC SCLEROSIS: A LONGITUDINAL STUDY. (June 2019) - Caimmi, Cristian; Bertoldo, Eugenia; Pozza, Alice; Caramaschi, Paola; Orsolini, Giovanni; Gatti, Davide; Rossini, Maurizio; Viapiana, Ombretta
Abstract : Background: Vitamin D is known to influence the immune system in many different diseases although longitudinal studies on systemic sclerosis (SSc) are still missing. Objectives: this study wants to investigate if variations in vitamin D serum levels (25OHD) over time affect digital ulcers (DU) in SSc. Methods: this is a retrospective study on 65 patients. Data on disease characteristics and 25OHD were collected in 2011 and 2016. Results: The mean age of our cohort was 58 (12) years with a mean disease duration of 9.5 (5.3) years. Most of our patients had a limited subset (69.2%). At baseline 50.8% and 41.5% after 5 years had 25OHD <30 ng. Supplemented patients (8750 IU) at baseline were 39 (60.0%) and 45 (69.2%) at the end of follow up. Nevertheless, 31 (47.7%) had a decrease of 25OHD in 5 years. In univariate analysis, patients with incident digital ulcers (DU) had a decrease in 25OHD as compared to patients with no incident DU (-17.4 (37.0) vs. 13.0 (89.5), p=0.018). No differences in 25OHD variations were found for other disease characteristics. In multivariate analysis correcting for previous DU and mRSS at baseline, patients with a decrease in 25OHD had an increased risk of developing DU (OR (IC95%): 16.6 (1.7 to 164.5), p=0.017). Conclusion: In this study we have shown that a decrease in 25OHD increases the risk of developing DUs and that vitamin D supplementation with the doses currently recommended may be insufficient in SSc. Further studies in wider cohorts are needed to confirm these results and to evaluate the effectiveness of a more aggressive or different vitamin D supplementation. Disclosure of interests: Cristian Caimmi: None declared, Eugenia Bertoldo: None declared, alice Pozza: None declared, Paola Caramaschi: None declared, Giovanni Orsolini Speakers bureau: Grunenthal, Davide Gatti Speakers bureau: abiogen, amgen, Janssen-Cilag, Mundipharma, Pfeizer, Maurizio Rossini: None declared, Ombretta Viapiana Speakers bureau: Novartis, abbvie, Eli-Lilly, Sanofi Genzyme